A Qualitative Analysis of the Socio-cultural Barriers to Intra-African Trade: Evidence from Nigerian Exporters - James, Edim Eka; Mishra, Rashmi; Varshney, Deepika; Jamie , Pepple, Grace; Eventus, Bernard, Samuel (Journal of Ecohumanism, 2024)
This study qualitatively analyzed the sociocultural barriers to intra-African trade, focusing on challenges faced by African businesses in cross-border markets, their impacts, and mitigation strategies. An exploratory case study design was adopted, using purposive and snowball sampling to select participants. Primary data were obtained through in-depth interviews with 10 members of the Association of Nigerian Exporters (ANE). Reflexivity and participant validation ensured research credibility, while Braun and Clarke’s reflexive thematic analysis framework guided data analysis, with thematic maps aiding interpretation. The findings identified five key sociocultural barriers substantially inhibiting intra-African trade: cultural complexity, corruption and bureaucratic obstacles, trust gaps, unhealthy rivalries, and business network challenges. These barriers contribute to miscommunication, failed negotiations, weakened consumer demand, failed partnerships, and increased operational costs for intra-African trade. These findings underscored that sociocultural factors play a pivotal role in shaping the success or failure of intra-African trade, highlighting the need for targeted strategies to address these barriers. In particular, they emphasized that cultural complexity hampers communication and negotiations, while corruption and bureaucratic obstacles erode trust and create inefficiencies. Trust gaps weaken partnerships, unhealthy rivalries hinder collaboration, and business network challenges limit market access and increase operational costs. Tackling these issues is crucial for improving trade efficiency and fostering stronger economic integration across the African continent.